Kepemimpinan Politik Lokal untuk Pengelolaan Hutan Berkelanjutan: Kasus di Provinsi Riau - Tiyas Tinov; Auradian Marta; Wan Asrida; Hasanuddin Hasanuddin; Ishak Ishak (Nakhoda: Jurnal Ilmu Pemerintahan, 2022)
Forest management is an interesting issue to discuss because it is closely related to the realization of the Sustainable Development Goals (SDGs), namely in handling climate change. The empirical phenomenon that occurs in Riau Province shows that there are still problems in forest management, resulting in deforestation and forest degradation, and forest tenure conflicts. Based on this, this study tries to answer the question what are the strategies used by the local political leadership and the challenges in forest management in Riau Province? This study used qualitative research methods. The research data comes from research informants, books, reports, research journals, and articles from news in the mass media and electronic media. Data analysis in this study uses a hermeneutic approach and analyzed using theories relevant to the research. The results of this study indicate that the strategy of local political leadership in forest management in Riau Province is in 4 (four) things, namely: (1) forest management planning; (2) forestry conflict prevention and resolution; and (3) forest and land fire prevention policies; and (4) forest and critical land rehabilitation. Meanwhile, the challenges faced by the local political leadership in forest management stem from the potential for corrupt behavior and a weak commitment to forest management. This study concludes that the strategy implemented by the local political leadership in Riau Province has not been able to realize sustainable forest management because of the weak commitment to sustainable forest management.